Correctional Educators’ Metaphorical Perceptions of Their Professional Selves (Papers in Arts and Humanities, 2025)
Metaphor is a widely studied phenomenon, valued not only for its aesthetic appeal and variety but also for its significant role in shaping thinking and cognition. In qualitative educational research, metaphors serve as valuable instruments for depicting existing educational states, revealing new insights into educational practice and theory, as well as for gaining a deeper understanding of educators’ world. Metaphors allow for linking information about one familiar concept to another, creating a new understanding through the comparison process that generates new meaning. Educators working in juvenile correctional institutions or reformatories form a rather under-researched community. As they carry out their educational activities in a closed world, there is limited information available about them. This study adopted a qualitative research design. Within the frame-work of semi-structured individual interviews conducted with fifteen correctional educators, I used the method of metaphor collection based on analogy, using the target concept of juvenile correctional educator. The resulting twenty-seven metaphors were organised into source concepts and subjected to content analysis. While the majority of the metaphors pertain to care and nurturing, others point to the closed nature of the institution, suggesting that the focus here is more on the role of the caregiver rather than that of the knowledge transmitter. With this method, my aim was to explore juvenile correctional educators’ most complex image of their own professional selves.
Keywords: metaphor; metaphor analysis; qualitative educational research; reformatory; correctional educator